Єременко О. Р., Пишна Д. Жанрово-стильові домінанти роману-біографії «Шрами на скалі» Р. Іваничука - Єременко О.; Пишна Д. (Philological Treatises, 2020)
The article deals with the defining features of biographical works; in the context of the creative works by R. Ivanychuk specifically mentioned individual and genre features of the novel "Scars on the rock.".